A Polish and German Population Study of Quality of Life, Well-Being, and Life Satisfaction in Older Adults During the COVID-19 Pandemic - Bidzan-Bluma, Ilona; Bidzan, Monika; Jurek, Paweł; Bidzan, Leszek; Knietzsch, Jessica; Stueck, Marcus; Bidzan, Mariola (Frontiers in Psychiatry, 2020)
Introduction Psychological studies undertaken during the COVID-19 pandemic rarely include people in their 60s. In our study, we studied the predictors of the quality of life, wellbeing, sleep and life satisfaction during the pandemic in older people from Germany and Poland, including factors such as risk behaviour, trait anxiety, feeling of threat, sleep quality, optimism, comparing them to three different age groups. Methods 494 adults in four groups: 60+ (N=60), 50-60 (N=139), 36-49 (N=155), <35 (N=140) completed validated self-report questionnaires assessing: socio-demographic data, quality of life, trait anxiety, risk tolerance, coronavirus threat, optimism regarding the pandemic, difficulty relaxing, life satisfaction, wellbeing, sleep quality during the pandemic period. Results Older people rated higher their quality higher of life than younger (mean difference = .74, SE = .19, p < .01) and middle-aged (mean difference = .79, SE = .18, p < .01), life satisfaction than younger (mean difference = 1.23, SE = .31, p < .01) and middle-aged (mean difference = .92, SE = .30, p < .05) as well as wellbeing higher than younger (mean difference = 1.40, SE = .31, p < .01) and middle-aged participants (mean difference = .91, SE = .31, p < .05), but experienced lower levels of trait anxiety and Coronavirus threat (mean difference = -9.19, SE = 1.90, p < .01), compared to younger age groups. They experienced greater risk tolerance (mean difference = 1.38, SE = .33, p < .01), as well as sleep quality (F=1.25; eta2=.01), optimism regarding the pandemic (F=1.96; eta2=.01), and had less difficulty relaxing during the pandemic (F=3.75; eta2=.02) than middle-aged respondents. Conclusions The findings show that the assessed quality of life, life satisfaction and wellbeing during pandemic is affected by the respondent’s age, trait anxiety and the threat of Coronavirus. Older people rated their quality higher of life, life satisfaction and wellbeing during pandemic higher than younger people, but experienced lower levels of trait anxiety and Coronavirus threat compared to younger age groups. They experienced greater risk tolerance, as well as sleep quality, optimism regarding the pandemic, and had less difficulty relaxing during the pandemic than middle-aged respondents.